Investigation of Zeta Potential of Water Based Nanomagnetite-Bentonite Dispersions - Pinter, Ákos; Zákányiné Mészáros, Renáta (International Journal of Engineering and Management Sciences, 2021)
The stability of different type nanomaterials play an important role among recent scientific and industrialchallenges, including the examination of the effect of polymers, surfactants and their mixture on surface and electric surface properties and aggregation extent of dispersed particles, which are of utmost importance. Bentonite and its composite with different nanomaterials are frequently used for instance in environmental protection for wastewater treatment, since due to their great specific surface area they have excellent sorption properties. There are several publications in the literature for the application of bentonite in drilling muds. By using them the fluid loss can be decreased during the drilling process, the filtration of the fluid can be increased, it also improves the rheological properties and the formation damage can also be mitigated. During research the investigation and the analysis of the zeta-potential of nanoparticles and their composites at different pH and salt content can be an interesting topic. During our experiments the electric surface properties of nanomagnetite synthetized in laboratory (NM), cationexchanged bentonite from Mád (Be) and the composite particles of these particles were investigated. Hybrid particles of different compositions (9:1, 7:3, 1:1, 3:7, 1:9) were analyzed at different potassium chloride concentrations (0.1 – 0.0001 M). The surface adsorption on the surface, i.e. the change in the surface charge can be traced well by analyzing the obtained zeta-potential values. The behavior of such systems was observed in the full pH interval, thus, valuable data were obtained regarding the colloidal stability. As for the stability, different requirements may emerge in practice, there are application fields where the colloidally stable system is advantageous, on the other hand, in some cases, ceasing the stabile system is the goal. Our investigations are of high importance in terms of stability and its characterization.